Educational Movement Against Hypertension and Diabetes (Gemes) in Prolanis Members: Gerakan Edukasi Mencegah Hipertensi dan Diabetes (Gemes) pada Anggota Prolanis - Rahmi Susanti; rania nasywa azzahra; Valendira Nuraini Putri; Dilla Camara Indriani; Siti Choirul Jannah Dewi Wijayanti; Senia Putri Yunita; Yuliana Pasha; Nabilla Nabilla (CONSEN: Indonesian Journal of Community Services and Engagement, 2025)
Coverage of the Minimum Service Standards (MSS) for hypertension and diabetes in Puskesmas Air Putih is still low, reaching only 11.31% and 26%, respectively, while the fulfillment of the quality of service for each type of basic service in the health MSS must reach 100%. The GEMES (Educational Movement to Prevent Hypertension and Diabetes) program is a public health intervention that aims to increase public knowledge, especially prolanis members, about hypertension and diabetes mellitus. The method used is counseling with a series of pre-test activities, distribution of leaflet media, presentation of material and questions and answers, post-test, and reaction. Based on the results of the program evaluation through the pre-test and post-test tested using the Wilcoxon Test, the p.value was (0.002 <0.05), then H0 was rejected so it was concluded that there was an increase in knowledge in participants before and after receiving material on hypertension and diabetes mellitus. To support the sustainability of the program, it is recommended that health counseling be carried out regularly with more interesting material so that information is broader and the program is more effective.